STRATEGI KOMUNIKASI PEMASARAN PRODUK IKAN BANDENG TANPA DURI PADA MASA PANDEMI COVID-19 DI UKM POKLAHSAR CAHAYA BANDENG MAROS - Amalia Anwar , Reski; Amin , Nurtaqwa; Muttaqin Mustari , Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Marketing is a way to introduce and promote a product with the aim that consumers can be interested and then end up with a transaction or exchange process between the seller and the buyer. The impact of the COVID-19 virus outbreak that hit the economic sector, especially for Small and Medium Enterprises, forced the public to adapt to the habits and lifestyles of the new normal era, as was experienced by UKM Poklahsar Cahaya Bandeng Maros. The research method used is a descriptive qualitative method which is useful for providing facts and data phenomena regarding the marketing communication strategy of thornless milkfish products in UKM Poklahsar Cahaya Bandeng Maros. The techniques used to collect data are interviews, documentation and observation. The results showed that the marketing communication strategy of the product thornless milkfish by UKM Poklahsar Cahaya Bandeng during the COVID-19 pandemic was by direct marketing, personal selling and public relations. The type of promotion used by Cahaya Bandeng SMEs in promoting their products during the COVID-19 pandemic is online, using social media such as Instagram. Facebook, WhatsApp and offline like door to door.